2011
DOI: 10.1128/aem.05864-11
|View full text |Cite
|
Sign up to set email alerts
|

Active Autotrophic Ammonia-Oxidizing Bacteria in Biofilm Enrichments from Simulated Creek Ecosystems at Two Ammonium Concentrations Respond to Temperature Manipulation

Abstract: The first step of nitrification, the oxidation of ammonia to nitrite, is important for reducing eutrophication in freshwater environments when coupled with anammox (anaerobic ammonium oxidation) or denitrification. We analyzed active formerly biofilm-associated aerobic ammonia-oxidizing communities originating from Ammerbach (AS) and Leutra South (LS) stream water (683 ؎ 550 [mean ؎ standard deviation] and 16 ؎ 7 M NH 4 ؉ , respectively) that were developed in a flow-channel experiment and incubated under thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 76 publications
(115 reference statements)
4
16
0
Order By: Relevance
“…The Nitrosospira cluster dominates in soils (59), and one sediment AOB sequence was affiliated with this group. Furthermore, BLAST results indicated that all AOB sequences in the water columns and some associated with sediment samples showed 98 to 100% identity to AOB sequences recovered from heavy fractions of a stable-isotope probing (SIP) experiment (60). Overall, these AOB sequencing results complement RT-qPCR results, which indicate important AOB contributions to ammonia oxidation in both subsurface sediments and water columns.…”
Section: Resultssupporting
confidence: 73%
“…The Nitrosospira cluster dominates in soils (59), and one sediment AOB sequence was affiliated with this group. Furthermore, BLAST results indicated that all AOB sequences in the water columns and some associated with sediment samples showed 98 to 100% identity to AOB sequences recovered from heavy fractions of a stable-isotope probing (SIP) experiment (60). Overall, these AOB sequencing results complement RT-qPCR results, which indicate important AOB contributions to ammonia oxidation in both subsurface sediments and water columns.…”
Section: Resultssupporting
confidence: 73%
“…Stable isotope probing (SIP) with 13 CO 2 has been used to study ammonia oxidizers (14) and, more recently, to distinguish between the relative autotrophic growth of AOB and AOA (15-19). Recently, it was shown for freshwater biofilms that AOB were actively assimilating 13 CO 2 at three different temperatures, whereas labeling of AOA was not observed (20).It is well known that temperature substantially affects the rate of biological reactions. With respect to nitrification, the rate in various environments increases gradually from Ͻ10°C to 30°C (21,22), reflecting the control of temperature on nitrifiers.…”
mentioning
confidence: 99%
“…Stable isotope probing (SIP) with 13 CO 2 has been used to study ammonia oxidizers (14) and, more recently, to distinguish between the relative autotrophic growth of AOB and AOA (15-19). Recently, it was shown for freshwater biofilms that AOB were actively assimilating 13 CO 2 at three different temperatures, whereas labeling of AOA was not observed (20).…”
mentioning
confidence: 99%
“…4A), contrary to most molecular-method-based studies, which have found Nitrosospira to be the major ammonium-oxidizing genus in agricultural soils (3,4,21,22,26). Fierer et al hypothesized that N additions may result in a shift from a more oligotrophic bacterial community to one that is more copiotrophic, analogous to a shift from K to r selection, terms often used to describe plant species ecology (13).…”
Section: Discussionmentioning
confidence: 64%
“…To stop the nitrification activity, 100 l 1% methiolate (ethylmercurithio-salicylic acid, sodium salt) was added to the subsamples, and the solutions were frozen and kept for chemical analyses. NH 4 ϩ , NO 3 Ϫ , and NO 2 Ϫ concentrations were later measured with a Lachat Autoanalyzer (Lachat Instruments, Milwaukee, WI).…”
Section: Methodsmentioning
confidence: 99%